Inhibition of Dimethylarginine Dimethylaminohydrolase (DDAH) Enzymes as an Emerging Therapeutic Strategy to Target Angiogenesis and Vasculogenic Mimicry in Cancer - Hulin, Julie-Ann; Gubareva, Ekaterina A.; Jarzebska, Natalia; Rodionov, Roman N.; Mangoni, Arduino A.; Tommasi, Sara (Frontiers in Oncology, 2020)
The small free radical gas nitric oxide (NO) plays a key role in various physiological and pathological processes through enhancement of endothelial cell survival and proliferation. In particular, NO has emerged as a molecule of interest in carcinogenesis and tumour progression due to its crucial role in various cancer-related events including cell invasion, metastasis and angiogenesis. The dimethylarginine dimethylaminohydrolase (DDAH) family of enzymes metabolise the endogenous nitric oxide synthase (NOS) inhibitors, asymmetric dimethylarginine (ADMA) and monomethyl arginine (L-NMMA), and are thus key for maintaining homeostatic control of NO. Dysregulation of the DDAH/ADMA/NO pathway resulting in increased local NO availability often promotes tumour growth, angiogenesis and vasculogenic mimicry. Recent literature has demonstrated increased DDAH expression in tumours of different origins and has also suggested a potential ADMA-independent role for DDAH enzymes in addition to their well-studied ADMA-mediated influence on NO. Inhibition of DDAH expression and/or activity in cell culture models and in vivo studies has indicated the potential therapeutic benefit of this pathway through inhibition of both angiogenesis and vasculogenic mimicry, and strategies for manipulating DDAH function in cancer are currently being actively pursued by several research groups. This review will thus provide a timely discussion on the expression, regulation and function of DDAH enzymes in regard to angiogenesis and vasculogenic mimicry, and will offer insight into the therapeutic potential of DDAH inhibition in cancer based on preclinical studies.